The Effectiveness of the Discovery Learning Model in Improving Understanding of Fiction Texts Among Fourth-Grade Students - Nafsiah Hayani; Rahmat Kartolo; Sutikno (PT Inovasi Pratama Internasional, 2026)
This research was motivated by the low level of students' understanding of fiction texts in the fourth grade of SD Negeri 152 Hutaraja, Mandailing Natal Regency. Preliminary observations revealed that most students had difficulty understanding story elements such as characters, plot, setting, and moral messages. Therefore, this study aims to determine the effectiveness of the Discovery Learning model in improving students’ understanding of fiction texts. This study employed a quasi-experimental design with a nonequivalent control group. The sample consisted of two classes: class IV A as the experimental group and class IV B as the control group, each consisting of 20 students. The experimental class was taught using the Discovery Learning model, while the control class was taught using conventional methods. The results showed that the average pre-test score in the experimental class was 62.3, which increased to 81.9 in the post-test, indicating an improvement of 19.6 points. Meanwhile, the control class improved from 62.8 to 72.2, with a gain of 9.4 points. The t-test analysis of the post-test data indicated that the t-value of 7.726 was greater than the t-table value of 2.10092 at the 5% significance level. This means that there was a significant difference in learning outcomes between the experimental and control groups after the treatment was given. Both classes had previously met the requirements for normality and homogeneity tests. These findings indicate that the Discovery Learning model is effective in improving students' comprehension in fiction text learning. The active, exploratory, and discovery-based learning process encouraged students to be more engaged in understanding the content and structure of stories, while also enhancing their curiosity and critical thinking skills. This model has also proven to create a more enjoyable and meaningful learning atmosphere, fostering collaboration and developing empathy through fictional stories